The Effect Of Game Training Methods On Improving Underhand Passing In Volleyball By Pst Bengkulu Athletes - Fransiskus Hendra Aribowo; Suwarni Suwarni; Feby Elra Perdima (Multidisciplinary Journals, 2026)
This study aims to determine the effect of game training methods on improving underhand passing in volleyball among PST Bengkulu athletes. This study used a quantitative approach with an experimental design to measure the effect of game training on improving PST Bengkulu athletes' underhand passing skills. The study subjects consisted of 32 athletes divided into two groups: an experimental group that participated in a drill training program and a control group that received no special intervention. Data analysis of the pre-test of the game training method group with a sample size of 32 obtained a highest score of 53, a lowest score of 41, an average of 46.96, and a median of 47. The post-test of the underhand passing group in the drill training method obtained a highest score of 59, a lowest score of 45, an average of 51.81, a median of 51.50, and a standard deviation of 3.93. The results of the paired t-test showed a calculated t value (10.14) that was greater than the t-table value (2.145), indicating that the research hypothesis was accepted. It can be concluded that the game training method has a significant influence on improving the underhand passing skills in volleyball of PST Bengkulu athletes.